Tourism Development Priorities in Lombok Eastern with Analytical Hierarchy Process - Kurniawan, Rinaldi; Kencana, Eka N.; Gandhiadi, G. K. (Universitas Muhammadiyah Mataram, 2022)
East Lombok is a regency that has tourism potential to be developed. In accelerating the pace of tourism development in East Lombok Regency, a decision support system is needed to make it easier to determine development priorities in the tourist sector. Analytical Hierarcy Process is a decision-making method that can solve the problem of multicriteria in the aspect of tourism in East Lombok. The data used are 50 data by prioritizing the opinions of experts and policy makers, namely the East Lombok Tourism Office, Head of tourism awareness groups and people involved in the tourism sector. The results showed that the value of index consistency was below 10% for each indicator and subindicator with infrastructure indicators as the highest priority with a value of 29.4545% and the highest subindicator was accessibility with a value of 17.8381%. The result of the calculation are expected to help policy makers in determining the strategy in the development of the tourism sector in Eaast Lombok district and in the future it can be developed by considering other factors.